Hubungan Tingkat Pengetahuan Dengan Kepatuhan Vaksinasi Covid-19 - Wijaya, Siswanto Agung; Wibowo, Nugroho Ari; Rahayu, Dian Putri (Indonesian Academia Health Sciences Journal, 2022)
Objective: to analyze the relationship between knowledge level and Covid-19 vaccination compliance in Suwaru, Kebonagung Sawahan Nganjuk. Methods: This study used a correlation analytic design with a cross sectional approach. The sample size of 81 respondents was taken using purposive sampling technique according to the inclusion and exclusion criteria. The independent variable is the level of knowledge and the dependent variable is Covid-19 vaccination compliance. The instrument used in this research is a questionnaire via google form. This study was analyzed using univariate and bivariate with Spearman rank correlation test Results: The results of the Spearman rank correlation test show the relationship between the level of knowledge and adherence to the Covid-19 vaccination p = 0.000 and the level of the correlation coefficient is 0.472. Conclusion: There is a relationship between the level of knowledge and compliance with Covid-19 vaccination in Suwaru, Kebonagung Sawahan Nganjuk, it is hoped that the community will increase the level of knowledge about the uses, benefits, side effects of Covid-19 vaccination to improve community compliance in carrying out Covid-19 vaccinations